Intervention in Massive Pulmonary Embolus: Catheter Thrombectomy/Thromboaspiration versus Systemic Lysis versus Surgical Thrombectomy - Moriarty, John M. (Semin Intervent Radiol, 2018)
Massive pulmonary embolus (PE), defined as hemodynamic shock from acute PE, is a life-threatening condition. Deaths from massive PE, especially when unsuspected, occur within minutes to hours of onset and as such prompt intervention can be lifesaving. Acute massive PE patients have traditionally been candidates for treatment with intravenous systemic thrombolysis to improve pulmonary artery pressure, arteriovenous oxygenation, and pulmonary perfusion in an effort to reduce mortality. However, patients with contraindications to systemic thrombolysis or those who have failed thrombolysis may benefit from other techniques including endovascular and surgical embolectomy. This article will review the current medical management as well as catheter-directed therapies and surgical embolectomy in the treatment of patients with massive PE.